Discrete regions of the avian beta-globin gene cluster have tissue-specific hypersensitivity to cleavage by sonication in nuclei. - Reneker, J S (1991)
We have analyzed the DNA released by sonication from avian nuclei, crosslinked with formaldehyde, by restriction mapping and equilibrium density gradient centrifugation. Our results indicate that regions flanking the adult beta-globin gene in adult reticulocytes have increased sensitivity to the mechanical shearing caused by sonication. These regions are near, and may overlap, the known nuclease hypersensitive regions that flank this gene. Like the hypersensitivity of these regions to nuclease digestion, the increased sensitivity to sonication is tissue-specific and appears to be due chiefly to the absence of nucleosome structures in these regions. Analysis of crosslinked chromatin fractionated by density gradient sedimentation suggests that DNA sequences near the matrix attachment region/enhancer element located 3' to the adult beta-globin gene are associated with transcriptionally-engaged chromatin fractions from both adult reticulocytes and day 5 chick embryo primitive erythroid cells. Sonication appears to be a useful tool for the study of chromatin structure.